Developing IT-Based Supplementary Listening Material for ‘Bahasa Inggris Kelas XII’ - Chatarina Catur Ani Trisnawati; Rr. Hasti Robiasih (Journal of English Language and Pedagogy, 2019)
This study is aimed at developing Informational Technology Based Supplementary Listening Material for ‘Bahasa Inggris Kelas XII’ and describing the effectiveness of the developed supplementary listening materials. The research belongs to an Educational Research and Development (R&D) and adopted the ten steps of Borg and Gall’s model (1983) which are simplified into three main stages. They are: (1) Preliminary Study, (2) Development and (3) Field Testing. The material development follows Nation and Macalister’s curriculum design model in which needs, environment and principles were taken into account in determining the content and sequence to achieve the goals, format and presentation of the materials and monitoring and assessment.  The developed listening materials consist of student work book and audio recording created with listening media and cool edit deluxe programs. The findings shows that (1) the developed IT based supplementary listening materials yields effective listening materials for the 12th grade students and (2) the effectiveness of the product helps students to achieve the targeted competences.